Investigation of interface characteristics and mechanical performances of Cu/Al plate fabricated by underwater explosive welding method - Jinhua Chen; Dapeng Zhou; Xiaohong Zhou; Hanliang Liang; Peizhong Feng; Yonghao Yu; Xueqin Kang (PLoS ONE, 2025)
Cu/Al composite plate was manufactured by underwater explosive welding method. The interface characteristics and mechanical properties of Cu/Al composite plate were evaluated and analyzed through phased array ultrasonic inspection, microstructure, uniaxial tensile test, three-point bending test, tensile shearing test and microhardness test. The results showed that the welding of thin Cu and Al plates is achieved by underwater explosive welding, with a Cu plate thickness of only 0.5 mm. A well bonded interface between Cu and Al plate is obtained, at a detonation velocity of 4 000 m/s, when the distance between Cu foil and Al plate is 0.2 mm. There are wavy fusion zones at the bonding interface of Cu/Al composite plate. No delamination or cracks are found at the bonding interface between Cu and Al during tensile and bending tests, and local cracking only occurs at the necking part in the tensile test due to severe deformation. The tensile strength and minimum tensile shearing strength of Cu/Al composite plate reaches 133 and 72.9 MPa, respectively. The hardness values of fusion zone, Cu and Al at the interface reach 385, 135 and 52 HV, respectively. The increase in hardness of Cu and Al near the interface is mainly caused by severed deformation induced by intense shock pressure.